Shape transformation of red blood cells induced by the osmotic pressure. (30th September 2020) - Yang, Zhen-Yu; Hou, Ji-Xuan
Abstract: We present a simple red blood cell (RBC) model and solve it only based on the variational method. Such a model allows us to obtain the morphological characteristics of human mature RBC under normal conditions, and to study its shape transformation induced by osmotic pressure. This study requires only modest computational capabilities and geometric knowledge and thus is well suited to be a part of an advanced physics or biophysics course.